Analysis of the Gene Expression and RNAi-Mediated Knockdown of Chitin Synthase from Leaf-Cutting Ant Atta sexdens - Moreira, Ariele C.; Carneiro, Renato L.; Fracola, Mariana F.; Micocci, Kelli C. [UNESP]; Bueno, Odair C. [UNESP]; Souza, Dulce H. F. (Soc Brasileira Quimica, 2020)
Chitin synthase (CHS) is the enzyme specifically associated with chitin synthesis, an important component of diverse organisms including insects. Two alternative spliced transcripts of the CHS gene (AsCHS-A1 and AsCHS-A2) were identified by quantitative reverse-transcription polymerase chain reaction (RT-qPCR) during the development of the leaf-cutting ant Ana sermons. Expression profiles of AsCHS-A transcripts increased from larva to pupae and decay in workers. Phylogenetic analysis showed both transcripts are classified within class A insect CASs. AsCI IS-A1 showed the highest expression level in larvae and pupae, while AsCHS-A2 is the main CHS transcript in workers. Our results suggest that these variants should be under regulation of different promoters. AsCHS-A1 has topology expected for insect CHSs, while the predicted AsCHS-A2 topology. with a missing A domain, is similar to some fungal CHSs. CHS-B (class B) was not identified in A. sexdens transcriptome. Ribonucleic acid interference (RNAi)-mediated gene silencing in pupae revealed that low reduction in CHS transcript levels (18%) was enough to cause morphological changes in the pupa exoskeleton impairing the process of cuticle sclerotization. To our knowledge, this work was the first to use and to show the feasibility of using RNA interference techniques on leaf-cutting ants.
Keywords: leaf-cutting ant; chitin synthase (CHS); CHS gene expression; RNAi-mediated knockdown; CHS insect topology